Analysis of Child-Friendly Schools in Building SDN Krebet 1 Sragen Student's Disciplined Character - Ris Fatma Pratiwi; Ani Rusilowati; Bambang Subali (Journal of Primary Education, 2022)
Child-friendly school education is an institution that plays a role in student’s character building, especially in the character of discipline. This study aims to analyze the application of child-friendly schools in shaping the disciplinary character of students at SD N Krebet 1 Sragen. It’s about the routine activities, spontaneous activities, exemplary activities, conditioning from the principal, teachers, and employees. This study uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. The research subjects are the principal, teachers, students, parents, and alumni. The validity test of the data using data triangulation method. The data were analysed by using Miles-Huberman data analysis techniques, namely data collection, data reduction, data display, and verification. From the results of the study, it can be concluded that Krebet 1 Sragen Elementary School has implemented the Child-Friendly School program in shaping the character of student discipline including school policies, implementation of the curriculum, the presence of educators and education staff, provision of facilities and infrastructure, participation of children of parents and alumni, then cultural activities school in class, school and outside school. The formation and inculcation of the character of discipline at SDN Krebet 1 Sragen include routine activities, spontaneous activities, exemplary activities, conditioning from the principal, teachers, and employees, as well as the role of parents and alumni in the school environment, discipline in time, discipline in dress, discipline in attending school activities such as students being greeted by the teacher in the morning, marching, singing traditional or national songs, reciting the Koran together (reading the asmaul husna, and iqro or the Qur’an), literacy, dhuha and dhuhur prayers in congregation, attending extra hours, then every Friday there is clean and healthy Friday, tausiyah and blessing Friday.